2004
DOI: 10.1023/b:item.0000008080.17926.2b
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Process Characteristics on the Value of B2B E-Procurement

Abstract: Abstract:In the previous chapter, we address the issue of value of B2B e-procurement by proposing a valuation framework. Of the three levels of factors identified, the process-related factors are closest to the locus of Web impact and most fundamental in determining the value. In this chapter, we focus on the effect of process characteristics on the value by the dual approach of empirical study and analytical modeling. We use an empirical study to highlight value differences caused by process types. We then de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 20 publications
0
36
0
1
Order By: Relevance
“…In relation to 1), coordination costs, such as search, negotiation, communication, follow-up, and error reconciliation with suppliers, can make up a significant part of costs and eprocurement can play a vital role in reducing such costs [19]. Earlier research found similar estimates of cost reductions due to the implementation of e-procurement.…”
Section: Research Objectivesmentioning
confidence: 91%
See 2 more Smart Citations
“…In relation to 1), coordination costs, such as search, negotiation, communication, follow-up, and error reconciliation with suppliers, can make up a significant part of costs and eprocurement can play a vital role in reducing such costs [19]. Earlier research found similar estimates of cost reductions due to the implementation of e-procurement.…”
Section: Research Objectivesmentioning
confidence: 91%
“…Despite the greater attention paid to the P2P, most companies are still unsure of the benefits and the ways to measure the value of the informatization of procurement, and which factors affect this value [19]. In many cases, the real benefits are not identified, resulting in companies not recognizing the true value of e-procurement [20].…”
Section: E-procurement: Benefits and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Adopters of e-procurement have reported gaining significant benefits (Croom & Brandon-Jones, 2007). According to Caniato et al (2011), these benefits can be grouped into two types: i) process benefits, such as reduced cost involved for processing orders due to error reduction (Ageshin, 2001, Nergiz and, shortened sourcing cycle time (Presutti, 2003), greater simplicity due to process streamlining, maverick buying reduction (Subramaniam & Shaw, 2004), and ii) organisational benefits, such as reduction in inventory costs (Ageshin, 2001), reduction in contract compliance (Subramaniam & Shaw, 2004), enhanced organisational image perceived by suppliers (Nergiz and Rahim, 2011;Rahim and Bintawal, 2012), greater decision support, and increased transparency (Rahim and As-Saber, 2011).…”
Section: Public E-procurement and The Use Of Social Media E-procurementmentioning
confidence: 99%
“…Furthermore, the number of activities may not be same for all types of businesses (Presutti, 2003). We have accepted major activities involved within e-procurement process suggested by Subramaniam and Shaw (2004) and grouped them in 4 stages: searching, order processing, monitoring and control and coordination. Based on our reading of the e-procurement literature, we have further identified several key activities involved in each of these stages.…”
Section: A Conceptual Modelmentioning
confidence: 99%